Change in albuminuria as a surrogate endpoint. Issue 6 (November 2019) - Waijer, Simke W.; Gansevoort, Ron T.; Heerspink, Hiddo J.L.
Abstract : Purpose of review: Chronic kidney disease is a global health problem with few effective therapies available that slow the progression to end-stage renal disease. The established clinical endpoints for renal trials; doubling of serum creatinine or end-stage renal disease, are late manifestations of CKD. This leads to large trials enrolling preferably patients with advanced stages of CKD. The use of valid surrogate biomarkers that substitute a clinical endpoint (surrogate endpoints), can lead to trials of shorter duration that can be performed at earlier stages of CKD. Change in albuminuria has been proposed as surrogate endpoint in CKD. Yet, although albuminuria is a strong risk factor for CKD progression, there is persistent uncertainty about its validity to substitute clinical endpoints. Recent findings: New observational studies have demonstrated robust associations between changes in albuminuria and risk of end-stage renal disease. In addition, a meta-analysis of observational studies confirmed the strong association between change in albuminuria and end-stage renal disease. Another meta-analysis of clinical trials showed moderately strong associations between treatment effects on albuminuria and treatment effects on clinical endpoints. These new data support a role for change in albuminuria as surrogate endpoint for clinical trials of progression of CKD. Summary: There is increasing evidence that change in albuminuria is a valid surrogate endpoint for CKD. Implementing albuminuria as surrogate requires proper understanding of the settings in which the surrogate works well.